Triggered release of model drug from AuNP-doped BSA nanocarriers in hair follicles using IRA radiation. (15th January 2016) - Lademann, J.; Richter, H.; Knorr, F.; Patzelt, A.; Darvin, M.E.; Rühl, E.; Cheung, K.Y.; Lai, K.K.; Renneberg, R.; Mak, W.C.
Graphical abstract: Triggered release of a fluorescent dye from gold nanoparticle-doped bovine serum albumin particles in hair follicles using infrared A radiation. Abstract: Recent advances in the field of dermatotherapy have resulted in research efforts focusing on the use of particle-based drug delivery systems for the stimuli-responsive release of drugs in the skin and skin appendages, i.e. hair follicles and sebaceous glands. However, effective and innocuous trigger mechanisms which result in the release of the drugs from the nanocarriers upon reaching the target structures are still lacking. For the first time, the present study demonstrated the photo-activated release of the model drug fluorescein isothiocyanate (FITC) from topically applied gold nanoparticle-doped bovine serum albumin (AuNPs-doped BSA) particles (approx. 545 nm) using water-filtered infrared A (IRA) radiation in the hair follicles of an ex vivo porcine skin model. The IRA radiation-induced plasmonic heating of the AuNPs results in the partial decomposition or opening of the albumin particles and release the model drug, while control particles without AuNPs show insignificant release. The results demonstrate the feasibility of using IRA radiation to induce release of encapsulated drugs from plasmonic nanocarriers for the targeting of follicular structures. However, the risk of radiation-induced skin damage subsequent to repeated applications of high infrared dosages may be significant. Future studies should aim at determining the suitability of lower infrared A dosages, such as for medical treatment regimens which may necessitate repeated exposure to therapeutics. Statement of significance: Follicular targeting using nanocarriers is of increasing importance in the prophylaxis and treatment of dermatological or other diseases. For the first time, the present study demonstrated the photo-activated release of the model drug fluorescein isothiocyanate (FITC) from topically applied gold nanoparticle-doped bovine serum albumin (AuNPs-doped BSA) particles using water-filtered infrared A (IRA) radiation in the hair follicles of an ex vivo porcine skin model. The results demonstrate the feasibility of using wIRA radiation to induce release of encapsulated drugs for the targeting of follicular structures, and provide a new vision on the development of optically addressable delivery systems for controlled release of drugs in the skin and skin appendages, i.e. hair follicles and sebaceous glands.